Afterword. Decentring and Renarrating Europe (One More Time): Echoes of War (One More Time) - Dialla, Ada A. (Historein, 2025)
This Afterword examines how the Russo-Ukrainian War and shifting geopolitics have reshaped historiography, particularly regarding Europe’s evolving borders, centres and peripheries. The war accelerated calls to decolonise Slavic, Russian and European studies, emphasising the agency of Ukraine. Ultimately, the war has reinvigorated debates about Europe’s identity, reminding scholars that Europe is not monolithic but a mosaic of shifting, intersecting regional, global and contested stories.